Biobanking in a Constantly Developing Medical World - Stefan-Alexandru Artene; Marius Eugen Ciurea; Stefana Oana Purcaru; Daniela Elise Tache; Ligia Gabriela Tataranu; Mihaela Lupu; Anica Dricu (The Scientific World Journal, 2013)
Biobank is a very sophisticated system that consists of a programmed storage of biological material and corresponding data. Biobanks are created to be used in medical research, in clinical and translational medicine, and in healthcare. In the past 20 years, a large number of biobanks have been set up around the world, to support the modern research directions in medicine such as omix and personalized medicine. More recently, embryonic and adult stem cell banks have been developed. Stem cell banking was reported to be required for medical research as well as clinical transplant applications. The quality of the samples stored in a biobank is very important. The standardization is also important; the biological material stored in a biobank must be processed in a manner that allows compatibility with other biobanks that preserve samples in the same field. In this paper, we review some issues related to biobanks purposes, quality, harmonization, and their financial and ethical aspects.